2015
DOI: 10.5603/ep.2015.0019
|View full text |Cite
|
Sign up to set email alerts
|

Radiojodoterapia w chorobie Gravesa-Basedowa — czynniki wpływające na skuteczność leczenia w oparciu o analizę retrospektywną

Abstract: Introduction: Radioiodine ( 131 I) isotope therapy is the method of choice in the treatment of Graves' disease relapse. The efficiency of this method is dependent on many factors; therefore, the present paper aims to identify the parameters that have a crucial impact on the efficacy of radioiodine therapy for Graves' disease. Material and methods:The authors performed a retrospective analysis of the medical documentation of 700 Graves' disease sufferers treated with 131 I. The patients were divided into three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 28 publications
(30 reference statements)
2
3
0
Order By: Relevance
“…This is in keeping with previous studies which have reported success of RIA therapy to be over 85% [41, 42]. …”
Section: Discussionsupporting
confidence: 92%
“…This is in keeping with previous studies which have reported success of RIA therapy to be over 85% [41, 42]. …”
Section: Discussionsupporting
confidence: 92%
“…The results suggested that, under similar conditions, men are more prone to developing NHRH compared to female patients, consistent with Allahabadia et al ( 21 ). DPUTV emerged as a protective factor against NHRH, indicating that a higher dose of 131 I relative to the thyroid weight correlates with a lower risk of NHRH, aligning with previous findings ( 22 , 23 ).…”
Section: Discussionsupporting
confidence: 90%
“…Markovic and colleagues reported that the chances of recovery are much greater for the patients with thyroids smaller than 62 g (9.6% of unsuccessful attempts) as opposed to patients with thyroids larger than 62 g (44% of cases of persistent hyperthyroidism) 13 . Szumowski et al 14 have proven that the volume of the thyroid gland has a significant ( P <0.002) effect on the success of treatment, and the larger the thyroid volume, the worse the treatment efficiency. Similar to the results of other studies, our study showed that the lower weight of the thyroid led to greater success of treatment ( P =0.002).…”
Section: Discussionmentioning
confidence: 99%
“…Several factors that affect the success of 131 I treatment in GD patients have been put forward, such as the dose of 131 I administration, thyroid volume, age, thyroid uptake of 131 I, and the use of antithyroid drugs 12 . Some researchers have proven that thyroid volume has a significant influence on the success of treatment and the inefficiency of 131 I therapy is closely related to thyroid volume 13 , 14 . The effect of age on the outcome of 131 I treatment is still a matter of debate.…”
Section: Introductionmentioning
confidence: 99%